A personagem feminina em The awakening, de kate Chopin - Zanatta, Deisi Luzia (2013)
This paper aims at analyz the female emancipation of the main character Edna Pontellier, in the novel The Awakening (1989), by North-American writer Kate Chopin. For this, is made an examination of the path taken by the main character in search of her liberation as a mother, wife and a woman that, by realizing herself as a subject, change her characteristics and behavior concerning the model of woman in the nineteenth century, historically and culturally conditioned by a patriarchal society. Serve as a theoretical support of this research essays of Antonio Candido and Anatol Rosenfeld included in the work A personagem de ficção, about the nature of fictional character and the studies of Edward Morgan Forster in Aspectos do romance on the classification of the characters. To substantiate the narrative voice, specifically narrator and narrative focus, are taking as reference the studies of Gérard Genette and Norman Friedman, which treats about heterodiegético narrator and selective and multiple selective omnisciense. Furthermore, the theoretical support of the historical background of women, emphasizing the period from Lilith to women in the nineteenth century, as well as the type of education that was intended provided to the woman that century, it has reference the studies of Michelle Perrot, Martha Robles, Simone de Beauvoir, Daniela Auad, Flavia Costa Morais and Virginia Woolf. The research showed that Kate Chopin presents the female condition in the nineteenth century and, by creating her heroine, Edna Pontellier, Chopin engenders in it her own thoughts as a writer and woman ahead of her time and disclosure the forms of abuse against woman